Analysis of Student Satisfaction with the Content and Teaching Methods of Agroindustrial and Environmental Entrepreneurship - Muhamad Hamdi; Saputra Ardhiyan; Setyaji Hajar (Agribusiness Journal, 2025)
This study aims to analyse student satisfaction with the content and teaching methods of the Agroindustrial and Environmental-Based Entrepreneurship course, which is crucial in shaping students' entrepreneurial mindset and skills in the context of sustainable development. The increasing demand for environmentally conscious entrepreneurs in the agroindustry sector highlights the significance of this course. The research uses a descriptive quantitative approach with a survey design involving 46 respondents. The results show that, in general, students are satisfied with the content, with an average score of 3.68, falling into the high category (3.41 - 4.20). Specific areas of satisfaction include content relevance to needs (3.85), content supporting entrepreneurial interest (3.78), content ease of understanding (3.62), and content applicability and contextuality (3.48). Satisfaction with teaching methods also indicates a high level (mean = 3.69), with interactive teaching (3.87), interesting case studies (3.73), discussions aiding understanding (3.65), and practical applications (3.50). External factors also show relatively high satisfaction (mean = 3.64), including classroom facilities (3.82), teaching aids quality (3.71), learning environment comfort (3.60), and availability of learning resources (3.41). The findings reveal that students from the Counselling and Guidance Study Program at the University of Jambi have high satisfaction with the course content and teaching methods. Despite high satisfaction, there are areas for improvement, such as enhancing the applicability of content and increasing the intensity of practical experience. External factors, such as classroom comfort and learning resources, should also be improved. To enhance learning quality, integrating more practical experiences and complex case studies, alongside digital technology and more applicable teaching materials, will enrich the learning experience. Further research in other programs and with a deeper approach will provide more comprehensive insights.